Increased Susceptibility of Rousettus aegyptiacus Bats to Respiratory SARS-CoV-2 Challenge Despite Its Distinct Tropism for Gut Epithelia in Bats - Björn-Patrick Mohl; Claudia Blaurock; Angele Breithaupt; Alexander Riek; John R. Speakman; Catherine Hambly; Marcel Bokelmann; Gang Pei; Balal Sadeghi; Anca Dorhoi; Anne Balkema-Buschmann (Viruses)
Increasing evidence suggests bats are the ancestral hosts of the majority of coronaviruses. In general, coronaviruses primarily target the gastrointestinal system, while some strains, especially Betacoronaviruses with the most relevant representatives SARS-CoV, MERS-CoV, and SARS-CoV-2, also cause severe respiratory disease in humans and other mammals. We previously reported the susceptibility of Rousettus aegyptiacus (Egyptian fruit bats) to intranasal SARS-CoV-2 infection. Here, we compared their permissiveness to an oral infection versus respiratory challenge (intranasal or orotracheal) by assessing virus shedding, host immune responses, tissue-specific pathology, and physiological parameters. While respiratory challenge with a moderate infection dose of 1 × 104 TCID50 caused a systemic infection with oral and nasal shedding of replication-competent virus, the oral challenge only induced nasal shedding of low levels of viral RNA. Even after a challenge with a higher infection dose of 1 × 106 TCID50, no replication-competent virus was detectable in any of the samples of the orally challenged bats. We postulate that SARS-CoV-2 is inactivated by HCl and digested by pepsin in the stomach of R. aegyptiacus, thereby decreasing the efficiency of an oral infection. Therefore, fecal shedding of RNA seems to depend on systemic dissemination upon respiratory infection. These findings may influence our general understanding of the pathophysiology of coronavirus infections in bats.